ANALISIS KRITIS TERHADAP STRATEGI MEMBANGUN KOMITMEN MUTU DI KALANGAN GURU - TIMORITA, YUDA AYU; Eko Handoyo; Fathur Rokhman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Background: Education is the main foundation in developing quality human resources. Improving the quality of education which is highly dependent on the role and commitment of teachers as the spearhead of the learning process, but various studies show that teacher commitment to quality is not evenly distributed, both in terms of understanding, involvement, and consistency of implementation. Objective: To critically analyze the strategy for building quality commitment among teachers. Method: A literature study of three related articles, namely “Increasing Teacher Commitment in the Framework of Improving School Quality” (Subban, 2021), “Strategy for the Development of Superior Madrasah by Building Teacher's Commitment to the Organization” (Widat. F, et al., 2022), “Impact of Teachers’ Commitment to the Relationship between Transformational Leadership and Sustainable Teaching Performance” (Alzoraiki, M., et al., 2023), using thematic content analysis techniques. Results: The strategy of building quality commitment among teachers can be applied in the school environment or educational institutions, based on managerial, psychological, and pedagogical approaches and must be collaborative, sustainable, and humane, the main key is empowering leadership, healthy school culture, facilitating meaningful teacher professional development, appreciation and recognition, and involving teachers in decision making as well as empowerment and professional autonomy. Conclusion: The success of improving the quality of education is highly dependent on the extent to which teachers have a strong professional commitment, both individually and collectively.